Pengaruh Status Sosial Ekonomi terhadap Partisipasi Masyarakat dalam Musrenbang (Musyawarah Perencanaan Pembangunan) Infrastruktur Jalan di Kecamatan Kradenan Kabupaten Blora - Septiana Cahyaningtyas; Edi Santosa; Lusia Astrika (Journal of Politic and Government Studies, 2014)
District of community participation Kradenan is worthy to be considered in conjunction with the Musrenbang (Council Development Plan). In a society there are social standing standing-called socio-economic status of the participation of the community planning forums (Council Development Plan). This study aims to determine the extent to which the relationship of socioeconomic status and community participation Musrenbang (Council Development Plan). The hypothesis of this study is no influence of socioeconomic status on the participation of the community planning forums (Council Development Plan) Infrastructure in District Kradenan. This study used a descriptive type with a sample of 96 people in the District Kradenan. The sampling technique used in this study is purposive sampling with sampling using the formula Frank Lynch. Data collection techniques by using questionnaires, interviews and documentation. Analysis of the data used is quantitative and qualitative. The tools used are simple regression. While hypothesis testing using t-test (t-test) and the coefficient of determination. Keywords that are used are socio-economic status, community participation, and planning forums (Council Development Plan) Infrastructure. The conclusion that there is a significant relationship and positively influence the socio-economic status of the community participation Musrenbang (Council Planning and Development) District of Kradenan not high2enough, because the socioeconomic status of the District Kradenan still low. The relationship of socio-economic status of the people of the District Kradenan 0.474 and the influence of socio-economic status of the community participation Musrenbang (Development Planning Meeting) by 5.22 percent. So it can be said that socio-economic status is not the dominant factor in influencing people's participation Musrenbang (Development Planning Meeting).Keyword : socioeconomic status, community participation, development planning, infrastructure